View of the Lock Hospital and its chapel, Kingsland - Wise, William; Schnebbelie, Robert Blemmell (Tufts Archival Research Center, 2008)
With the interior of the chapel. This illustration is from Robert Wilkinson's "Londina Illustrata," vol. 1.